Examining school librarians’ readiness for information literacy education implementation - Tan, Shyh-Mee; K., Kiran; S., Diljit; Tan, Shyh-Mee; Kiran, K.; Diljit, S. (Malaysian Journal of Library and Information Science, 2017)
Shyh-Mee, T., Kiran, K., & Diljit, S. (2016). Examining school librarians’ readiness for information literacy education implementation. Malaysian Journal of Library & Information Science, Vol.20, no. 1: 79-97. This study investigates how school librarians perceive their readiness in implementing information literacy (IL) education in schools. It addresses the concern that school librarians may not be adequately prepared in delivering the IL programmes in schools. This study uses a quantitative research approach with two data collection techniques; i.e. semi-structured interviews with eight school librarians and district officers, and a survey involving 710 school librarians from secondary schools in Malaysia. The school librarians’ readiness construct is derived from the cognitive, functional and technical sub-scales of IL education implementation readiness. It was found that school librarians’ professional qualification has an impact on their cognitive, functional and technical readiness. However, their experience as a school librarian had an impact on technical readiness only. The study emphasizes school librarians’ readiness as a factor in the successful implementation of information literacy education in Malaysian schools.